Energy Storage: An All‐Solid‐State Flexible Piezoelectric High‐k Film Functioning as Both a Generator and In Situ Storage Unit (Adv. Funct. Mater. 45/2015). (December 2015) - Tong, Wangshu; Zhang, Yihe; Zhang, Qian; Luan, Xinglong; Lv, Fengzhu; Liu, Leipeng; An, Qi
Abstract : Y. Zhang, Q. An, and co‐workers present all‐solid‐state flexible films that simultaneously convert low‐frequency biomechanical energy to electricity and store the energy for later release. This design is realized by employing PVDF‐HFP in the simultaneous dual role of piezoelectric generator and polymer matrix of the flexible capacitor. Surface‐modified reduced graphene oxide fillers are indispensable in achieving the superior energy‐storage performance of the film.